Oral health-related quality of life and associated factors among homeless people in Malaysia / Dewi Mayang Sari Kamarozaman - Dewi Mayang Sari, Kamarozaman (2022)
Introduction: Despite the increased number of homeless people in Malaysia, limited information is available on their oral health status and oral health-related quality of life (OHRQoL). This study aimed to investigate the impact of clinical factors (oral health status) and individual factors (dental anxiety, depression, oral health [OH] knowledge, attitude towards OH service, OH behaviours and high-risk behaviours) on the OHRQoL of Malaysian homeless adults and to determine the mediation role of OH status on OHRQoL. Method: A cross-sectional study involving homeless persons was conducted in five states in Malaysia using a validated questionnaire. To determine the relationship between OHRQoL, individual, and clinical factors, the theoretical models proposed by Wilson and Cleary (1995) and Brunner and Marmot (2006) were modified and used to conceptualise the study. The demographic, socioeconomic and medical condition information were obtained as a background information and confounding factors. To examine the caries experience and periodontal status, the decay-missing-filled-teeth (DMFT) index and basic periodontal examination (BPE) were used respectively. As for assessing the OHRQoL of the homeless, oral health impact profile (OHIP-14) was used where higher score indicates poorer OHRQoL. Also, the Modified Dental Anxiety Scale (MDAS) and the Depression component of DASS-21 (Depression Anxiety and Stress Scale) were used to measure dental anxiety and depression respectively. The descriptive and bivariate analyses of the data were performed using SPSS. To test the hypotheses of this study, partial least squares equation modelling (PLS-SEM) was conducted using SmartPLS. Results: A total of 192 homeless people completed the questionnaire and oral examination. The majority were male (84.9%), with a mean age of 43.72 (SD=11.4). A total of 37.5% of participants were street homeless (primary homeless) and 56.3% were jobless. Majority (86.5%) reported having at least one medical condition or required iv medical treatment in the last six months. The prevalence of dental caries was 89.6%, with a mean DMFT of 9.39 (SD=7.59). Almost two-fifth (17.3%) had poor oral hygiene and 97.3% showed signs of periodontal disease. OHRQoL impact was reported by 72.9% of the participants, with a mean OHIP score of 18.61(SD=11.3). The prevalence of dental anxiety, dental phobia and depression was 63%, 10% and 52.1%, respectively. In total, 58.9% of the participants had good oral health knowledge. All participants had at least two negative attitudes towards OH service. In terms of oral health behaviour, 86.5% brushed their teeth at least once a day, 74.9% used fluoridated toothpaste, 57.8% had low sugar intake and 18.2% had their dental visit in the last 12 months. Majority (81.3%) had engaged in at least one high-risk behaviour. Thirty percent of the variance in OHRQoL could be explained by OH status and individual factors. The path coefficients between OH status and OHRQoL impact was the strongest (β=0.368, P<0.001). High-risk behaviours directly influenced OHRQoL (β=0.142, P<0.01), and indirectly through OH status (β=0.199, P<0.01). Significant relationships were found between homeless’ dental anxiety (β=0.238, P<0.001) and depression levels (β=0.234, P<0.001), with OHRQoL impact. Conclusion: OH status and individual factors (dental anxiety, depression and high-risk behaviours) are the predictors of homeless’ OHRQoL. OH status was the most significant predictor that contributed the largest amount to the model. The findings emphasize the importance of OH health care delivery for the homeless, including curative care to address the influential clinical factors. The empirical evidence of this study could facilitate the planning of targeted strategies by incorporating reduction in dental anxiety, social support enhancement, OH promotion and management of high-risk behaviours for the homeless in Malaysia. Keywords: Homeless, inequality, oral health, oral health related quality of life, vulnerable population